Evaluation of the NUV forecast performance against ground-based measurements in southern South America - Orte, Facundo (2024)
Fil: Orte, Facundo. Instituto de Investigaciones Científicas y Técnicas para la Defensa. Departamento de Investigaciones en Láseres y sus aplicaciones; Argentina